An Example of a Special Algorithm Application for Control of Aerial Guided Bomb Flight, during Guidance on the Ground Moving Target - Stefanski, Konrad (Applied mechanics and materials, 2016)
This paper presents the analysis of the variety of methods regarding aerial guided bomb control during the ground attack on a moving target. Based on this method there was an earlier research regarding motion control of the three degrees of freedom gyroscope axis [1,2] during space exploration and discovered target tracking. Positive results obtained during that research led to conclusion that the proposed control method will be accurate to establish a control force for aerial bomb guiding. This method is based on the use of phase trajectories control deviations. Switching of the control forces in the particular phase plane points causes the deviations to decrease to zero and facilitates the proper trajectory of the bomb. This paper presents a switching algorithm, equations of kinematics and dynamics of a bomb flight-path and the variety of examples of a numerical simulations. Obtained results were presented in the graphic form.